Vultos de vestígios – a poética de uma lembrança - Frauzino, Christiane Cavalcante (2015)
The present article evoke memories from my childhood and bring to present poetic elements that I will to construct a project for site specific. Images-memories of the past came into my mind like photographs. The memory like a poetic territory envolve and put together past and present on the same line, breaking boundaries. The images used to make the curtains, were printed from woodcut , pieces of old floorboard. Between present and past, images and memories, i try to connect ideas to propose possilites dialogues poetic.